Peach Fuzz: Conceptual Engineering of Color Categories - Yu. A. Griber (Научный диалог, 2024)
This article explores the products of conceptual engineering in contemporary media communication and mass culture. The analysis examines the mechanisms and communicative consequences of intentionally creating color categories. The shade known as peach fuzz, selected by the Pantone Institute as the color of the year 2024, is used as a case study. It is shown that in the case of the color of the year, the transmission of the conceptual idea involves two channels simultaneously (visual and verbal), each in two different forms. The author notes that the visual channel is used to ostensively present the shade with specific chromatic characteristics and to develope a complex visual image on this basis. Special attention is paid to the verbal channel, which is utilized in the form of intentionally constructed color designations and supporting stories (conceptual myths). It is concluded that from the perspective of color communication, verbal and visual texts serve fundamentally different functions. The visual representation shows how the viewer should see the color, while the verbal explanation clarifies why this shade is needed. It is demonstrated that the image embedded in the color name sets the desired connotation, which can transform the perception of the shade by adding necessary meanings to it. The verbal story defines a cognitive “point of view” for introducing a new category into an existing color system.